2019
DOI: 10.1109/access.2019.2933323
|View full text |Cite
|
Sign up to set email alerts
|

Towards Coexistence of Cellular and WiFi Networks in Unlicensed Spectrum: A Neural Networks Based Approach

Abstract: Long-Term Evolution in the Unlicensed Spectrum (LTE-U) is considered as an indispensable technology to mitigate the spectrum scarcity in wireless networks. Typical LTE transmissions are contentionfree and centrally controlled by the Base Station (BS). However, the wireless networks that work in unlicensed bands use contention-based protocols for channel access, which raise the need to derive an efficient and fair coexistence mechanism among different radio access networks. In this paper, we propose a novel mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Whereas, the system model we consider in this work is based on the uplink communication and employs a time division multiplexing based solution. Hence, the perspective of resource sharing is different in comparison to [40] and [41]. Note that we do not advocate that one model is better than the other and believe that different access schemes are designed to serve different purposes.…”
Section: A Related Workmentioning
confidence: 91%
See 1 more Smart Citation
“…Whereas, the system model we consider in this work is based on the uplink communication and employs a time division multiplexing based solution. Hence, the perspective of resource sharing is different in comparison to [40] and [41]. Note that we do not advocate that one model is better than the other and believe that different access schemes are designed to serve different purposes.…”
Section: A Related Workmentioning
confidence: 91%
“…The work in [40] considers LTE supplemental downlink (SDL) methodology which is used only in the downlink to support higher downlink support for LTE stations. The work in [41], on the other hand, employs an alternating slot assignment model which assigns different time slots to LTE-U BS or Wi-Fi stations. Whereas, the system model we consider in this work is based on the uplink communication and employs a time division multiplexing based solution.…”
Section: A Related Workmentioning
confidence: 99%
“…Besides, no similar work is found in the literature for comparison. In [17], the authors suggested a new mechanism based on neural networks for the coexistence of an LTE-U base station in the unlicensed spectrum accompany by WiFi-6 access points. The obtained numerical results in this paper show that the suggested algorithm can provide the way for LTE-U base station to work efficiently in the unlicensed spectrum while protecting Wi-Fi users with 90% fairness.…”
Section: Related Workmentioning
confidence: 99%
“…allocation of spectrum in the 37 GHz bands for shared access and above 90 GHz for unlicensed access. Since Long Term Evolution (LTE) Release-13, cellular communications have expanded their paradigm of operation to the unlicensed spectrum bands [6], [7]. For LTE, the main focus has been on the unlicensed 5 GHz bands, for which multiple LTE variants are currently available, namely Licensed-Assisted Access (LAA) (in 3GPP Release-13, 14 and 15) [8]- [12], LTE Unlicensed (LTE-U) (developed by the LTE-U Forum based on LTE Release-12) [6], [13] and MulteFire (developed by the MulteFire Alliance based on LTE Release-14) [14], [15].…”
Section: Introductionmentioning
confidence: 99%